Perdagangan Organ Tubuh Manusia Sebagai Kejahatan Lintas Negara - Fadillah, Astuti Nur; Mahmud, Abbas (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Transplantation is intended to replace a damaged or functioning organ in the recipient with another organ that is still functioning from the donor. Technological developments in the world of health not only have a positive impact on the world of medicine but also open up opportunities for illegal human organ trading syndicates. Human organ trafficking is a type of transnational crime that has occurred frequently in recent decades.Purposes of the Research: Aims to analyze human organ trafficking as a transnational crime.Methods of the Research: The research method used is normative juridical.Results of the Research: Illegal trade in human organs involving cross-border syndicates is a transnational crime. Cross-border crime is a threat that is taken seriously by each country because it threatens the security and stability of the country. To prevent this, countries can work together with each other. with each other through bilateral agreements, one of which is the extradition agreement, to stop the practice of selling and buying human organs. It is hoped that the implementation of laws and regulations related to human organ crimes will run smoothly so that the perpetrators can be charged using existing regulations. So transplants can only be carried out for humanitarian purposes and can only be carried out in certain health facilities by health workers who have the expertise and authority to do so.